Poly (hexamethylene biguanide), adsorbed onto Ti‐Al‐V alloys, kills slime‐producing Staphylococci and Pseudomonas aeruginosa without inhibiting SaOs‐2 cell differentiation. Issue 5 (27th November 2019) - Hornschuh, Melanie; Zwicker, Paula; Schmidt, Thomas; Finke, Birgit; Kramer, Axel; Müller, Gerald
Abstract: Antimicrobial coating of implant material with poly(hexamethylene biguanide) hydrochloride (PHMB) may be an eligible method for preventing implant‐associated infections. In the present study, an antibacterial effective amount of PHMB is adsorbed on the surface of titanium alloy after simple chemical pretreatment. Either oxidation with 5% H2 O2 for 24 hr or processing for 2 hr in 5 M NaOH provides the base for the subsequent formation of a relatively stable self‐assembled PHMB layer. Compared with an untreated control group, adsorbed PHMB produces no adverse effects on SaOs‐2 cells within 48 hr cell culture, but promotes the initial attachment and spreading of the osteoblasts within 15 min. Specimens were inoculated with slime‐producing bacteria to simulate a perioperative infection. Adsorbed PHMB reacts bactericidally against Staphylococcus aureus, Staphylococcus epidermidis, and Pseudomonas aeruginosa after surface contact. Adhered SaOs‐2 cells differentiate and produce alkaline phosphatase and deposit calcium within 4 days in a mineralization medium on PHMB‐coated Ti6Al4V surfaces, which have been precontaminated with S. epidermidis . The presented procedures provide a simple method for generating biocompatibly and antimicrobially effective implant surfaces that may be clinically important.